PENINGKATAN KEMAMPUAN MENULIS TEKS DRAMA DENGAN MENGGUNAKAN MODEL MEA (MEANS ENDS ANALYSIS) SISWA KELAS VIII - Waruwu, Lestari (Universitas Lampung, 2024)
The purpose of this study is to improve students' ability to write drama texts using the MEA (Means Ends Analysis) model. To achieve these objectives, this study used the Classroom Action Research method with the implementation procedures are: planning, action, observation, and reflection. This Classroom Action Research activity was carried out in two cycles using data collection techniques, observation sheets and assessment sheets. The subjects of this study were VIII grade students of SMP Negeri 1 Tuhemberua with a total of 34 students with 18 males and 16 females conducted in the even semester of the 2018/2019 Learning Year. The results of the study showed that there was an increase in students' ability to write drama texts using the MEA (Means Ends Analysis) model. This, seen in the results of cycle I, the lowest score was 40 while the highest score was 80 with an average score of 57.11 while in cycle II with the lowest score of 70 while the highest score was 94 with an average score of 76.32. The results of the observation of researchers in cycle I, the first meeting amounted to 45.45% and the second meeting amounted to 63.63%. While cycle II, the first meeting amounted to 72.72% and the second meeting amounted to 100%. The results of student observation in cycle I, the first meeting was 26.20% and the second meeting was 41.17%. While the observation results in cycle II, namely the first meeting amounted to 63.37% and the second meeting amounted to 100%. Tujuan penelitian ini adalah untuk meningkatkan kemampuan siswa menulis teks drama dengan menggunakan model MEA (Means Ends Analysis). Untuk mencapai tujuan tersebut, penelitian ini menggunakan metode Penelitian Tindakan Kelas dengan prosedur pelaksanaannya adalah: perencanaan, tindakan, observasi, dan refleksi. Kegiatan Penelitian Tindakan Kelas ini dilaksanakan dua siklus dengan menggunakan teknik pengumpulan data, lembar observasi dan lembar penilaian. Subjek penelitian ini adalah siswa kelas VIII SMP Negeri 1 Tuhemberua dengan jumlah siswa 34 orang dengan jumlah laki-laki 18 orang dan perempuan 16 orang yang dilaksanakan pada semester genap Tahun Pembelajaran 2018/2019. Hasil penelitian, ada peningkatan kemampuan siswa menulis teks drama dengan menggunakan model MEA (Means Ends Analysis). Hal ini, terlihat pada hasil siklus I nilai nilai terendah 40 sedangkan nilai tertinggi 80 dengan rata-rata nilai sebesar 57,11 Sedangkan pada siklus II dengan nilai terendah 70 sedangkan nilai tertinggi 94 dengan rata-rata nilai sebesar 76,32. Hasil observasi peneliti siklus I pertemuan pertama sebesar 45,45% dan pertemuan kedua sebesar 63,63%. Sedangkan siklus II yaitu pertemuan pertama sebesar 72,72% dan pertemuan kedua sebesar 100%. Hasil observasi siswa siklus I pertemuan pertama 26,20% dan pertemuan kedua sebesar 41,17%. Sedangkan hasil observasi pada siklus II yaitu pertemuan pertama sebesar 63,37% dan pertemuan kedua sebesar 100%.